Percutaneous Medial Collateral Ligament Repair and Posteromedial Corner Repair With Suture Tape Augmentation - Hopper, Graeme P. (Arthrosc Tech, 2020)
The medial collateral ligament (MCL) is among the most commonly injured structures of the knee. Most cases are managed nonoperatively; however, grade III injuries and injuries associated with multiligament injuries to the knee are often managed surgically. MCL reconstruction procedures are the most widely used surgical option, but modern advancements have seen a renewed interest in ligamentous repair that avoids graft-site morbidity. In addition, augmentation of the repair protects the ligament during the healing phase and allows early mobilization. This article describes, with video illustration, percutaneous MCL repair and posteromedial corner repair with suture tape augmentation.